Closed mallet thumb injury treated surgically: a case report. Issue 1 (1st January 2017) - Arvanitakis, Michael; Calcagni, Maurizio; Giesen, Thomas
Abstract: In this report a case of closed mallet thumb injury is described, which was diagnosed clinically and indication for surgical treatment was confirmed with ultrasound examination. The EPL-tendon was successfully reconstructed with an excellent result. We propose a mandatory ultrasound examination of all closed mallet thumb injuries.